1998
DOI: 10.1038/sj.ijo.0800716
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence of obesity among Belgian men at work, 1977–1992

Abstract: OBJECTIVE: To assess trends in average body mass index (BMI) and the prevalence of obesity between 1977 and 1992, in middle-aged Belgian men at work. SUBJECTS: A subsample of men at work, aged 40 ± 54 y extracted from the base-line data from four independent prospective studies, each representing a period (Physical Fitness Study (1977 ± 1978, Belgian Interuniversity Research on Nutrition and Health (BIRNH) (1979 ± 1984), Multinational Monitoring of Trends and Determinants in Cardiovascular Diseases (MONICA) (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
1
4
2
Order By: Relevance
“…Those findings do not replicate those of other studies conducted in France, 5 Spain, 12 Belgium, 13 or the USA, 3 although the increase among age group 45 -54 y is consistent with other studies. 13 The reasons for such a differential increase are not straightforward and remain to be assessed. Data are presented as percentage and (number of overweight or obese subjects=all subjects in age group).…”
contrasting
confidence: 83%
“…Those findings do not replicate those of other studies conducted in France, 5 Spain, 12 Belgium, 13 or the USA, 3 although the increase among age group 45 -54 y is consistent with other studies. 13 The reasons for such a differential increase are not straightforward and remain to be assessed. Data are presented as percentage and (number of overweight or obese subjects=all subjects in age group).…”
contrasting
confidence: 83%
“…Similar trends have been reported also in other European countries: Sweden, 22,23 The Netherlands, 24 Germany, 25 Spain 26 and Belgium. 27 The shifts in our study, however, were not as steep as in the UK, where the prevalence of obesity has doubled from 1980 to 1994. 28 The prevalence of obesity in Finland (20%) is high compared to the other Nordic countries in the 1980s.…”
Section: Discussioncontrasting
confidence: 56%
“…Many studies have reported a similar association for men. Recent trend studies have shown that during the last decades, socioeconomic differences in obesity have persisted and even widened in many countries (3,4,5), including Finland (6,7). A better understanding of socioeconomic differences in obesity is, therefore, increasingly important for attempts to narrow such differences and reduce the overall prevalence of obesity.…”
Section: Introductionmentioning
confidence: 99%